Candidate cytomegalovirus strain for human vaccination. - Plotkin, S A (1975)
A strain of human cytomegalovirus called Towne was isolated in WI-38 human fibrolast cell cultures from the urine of an infected infant. It was then passaged 125 times in WI-38, including three clonings, and a pool was prepared in the same cell substrate for use as a potential live attenuated vaccine. The Towne virus has a broad antigenicity and cross-reacts with the AD-169 strain. Several markers of the Towne virus were found which differentiated it from fresh isolates. One of these was resistance of the former to trypsin. The Towne virus was tested for freedom from oncogenicity or other harmful effects in preparation for tests in humans.